Environmental enrichment models a naturalistic form of maternal separation and shapes the anxiety response patterns of offspring. (February 2015) - Connors, E.J.; Migliore, M.M.; Pillsbury, S.L.; Shaik, A.N.; Kentner, A.C.
Highlights: We evaluated maternal care and juvenile offspring behavior following pre- and postnatal environmental enrichment (EE). EE increased offspring GLUR1 and GABA concentrations in prefrontal cortex of both sexes; increased glutamate level was only observed in males. Male and female EE offspring demonstrated anxiety-like behavior on the elevated plus maze and light dark test, but not when engaged in social interaction. Overall, early-life EE promotes flexible response patterns between novel vs. familiar anxiety-provoking contexts. Summary: Environmental enrichment (EE) mimics positive life experiences by providing enhanced social and physical stimulation. Placement into EE following weaning, or in later life, confers beneficial outcomes on both emotional and cognitive processes. However, anxiety-like behavior is also reported, particularly in rats exposed to enhanced housing during early development. Notably, the quality of maternal behavior affects stress regulation and emotional stability in offspring, yet the impact of environmental context on maternal care has not been thoroughly evaluated, or are the influences of EE on their offspring understood. To investigate the role of EE on these factors we analyzed the details of mother-neonate interactions, and juvenile offspring performance on several anxiety measures. Additionally, we evaluated neurochemical differences (i.e. serotonin, corticosterone, GABA, glutamate) in prefrontal cortex and hippocampus as a function of EE, Communal Nesting (CN) and Standard Care (SC). Although EE dams spent significantly less time on the nest and had lower nursing frequencies compared to SC dams, there were no differences in maternal licking/grooming. In offspring, EE increased GLUR1 level and GABA concentrations in the prefrontal cortex of both juvenile male and female rats. A similar pattern for glutamate was only observed in males. Although EE offspring spent less time on the open arms of the elevated plus maze and had faster escape latencies in a light-dark test, there were no other indications of anxiety-like behavior on these measures or when engaged in social interaction with a conspecific. In the wild, rats live in complicated and variable environments. Consequently dams must leave their nest to defend and forage, limiting their duration of direct contact. EE exposure in early development may mimic this naturalistic maternal separation, shaping parental behavior and offspring resiliency to stressors.